The PM and the pendulum dynamic forecasting of British elections. - Lebo, Matthew J.; Norpoth, Helmut (British Journal of Political Science, 2007)
We apply a dynamic perspective to forecasting votes and seats in British elections. Our vote model captures the swing of the electoral pendulum between the two major parties while using prime ministerial approval as the (sole) short-run predictor of vote choice.